2009
DOI: 10.1177/0018726709349198
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of the curvilinear relation between extent of telecommuting and job and life satisfaction: The role of performance outcome orientation and worker type

Abstract: The purpose of this study is to determine factors that are related to employee satisfaction with telecommuting. Recent research supports the notion of a curvilinear relation between extent of telecommuting and job satisfaction. Drawing on control theory, we find that performance outcome orientation (degree to which objective criteria are used in employee evaluation) moderates the curvilinear relation between extent of telecommuting and job satisfaction. We also find support for a curvilinear (inverted U) relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 44 publications
10
104
1
3
Order By: Relevance
“…This study showed a slight, but still statistically significant association with lifesatisfaction. A similar finding was made by Virick et al (2010) in connection to telecommuting and life-satisfaction. However, in their study the relation was curvilinear and mediated by work drive and work enjoyment.…”
Section: Resultssupporting
confidence: 84%
“…This study showed a slight, but still statistically significant association with lifesatisfaction. A similar finding was made by Virick et al (2010) in connection to telecommuting and life-satisfaction. However, in their study the relation was curvilinear and mediated by work drive and work enjoyment.…”
Section: Resultssupporting
confidence: 84%
“…Virtual work can reduce work stress (Raghuram & Wiesenfeld 2004) and increase feelings of autonomy (Kelliher & Anderson 2008), organizational commitment (Hunton & Norman 2010), job satisfaction (Virick et al 2010), and job performance (including extrarole behaviors) (Bloom et al 2015, Gajendran et al 2015, Gajendran & Harrison 2007. One meta-analysis found that telecommuting reduces work-family conflict by helping workers juggle professional and personal work (Gajendran & Harrison 2007).…”
Section: Flexibility In Where Work Is Accomplishedmentioning
confidence: 99%
“…Specifically, Cooper and Kurland (2002) argued that decreased interactions with coworkers resulting from teleworking, coupled with increased feelings of isolation, led to lower levels of job satisfaction. Several other factors, such as lack of professional support, impeded career advancement and an "out of sight, out of mind" mentality among teleworkers has been related to lower job satisfaction levels as well (Virick et al, 2010).…”
Section: Teleworking and Job Satisfactionmentioning
confidence: 99%